PENGARUH MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2017-2019) - Mitha Christina Ginting; Lamria Sagala (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2020)
This study aims to determine and analyze the effect of intellectual capital on firm value. Intellectual capital is measured using the Value Added Intellectual Coefficient (VAIC) model. Firm value is measured using Price to Book Value (PBV), Earning per Share (EPS), and Price Earning Ratio (PER). The population of this research is manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The number of samples of this study were 25 companies selected based on the sampling technique using purposive sampling technique. Because this study uses secondary data with three years of observation, the total number of observations is 75 (25 companies X 3 years). Methods of data analysis using multiple linear regression. Data received and collected were processed using the SPSS version 22 application. The results showed that Intellectual Capital had a negative and insignificant effect on Firm Value as measured by Price to Book Value (PBV) and Intellectual Capital had a positive and insignificant effect on Firm Value as measured by Earning Per Share (EPS), however, Intellectual Capital has a negative and significant effect on Firm Value as measured by Price Earning Ratio (PER).